Analisis Efisiensi Proses Drafting 2D Dies pada Empat Proses Dies Menggunakan Metode Diagram Fishbone melalui Integrasi Siemens NX 7.5 - Avifan Septianto; Rafli Alfandi; Muhammad Iqbal; Akmal Arfie; Yudi Prasetyo (INDO PUBLISHING, 2026)
The 2D dies drafting process in the manufacturing industry plays an important role in supporting tooling dies production. A common problem encountered is the use of different software platforms between Siemens NX for 3D modeling and AutoCAD for 2D drafting, resulting in longer processing times, potential data inconsistencies, and increased file storage requirements. This study aims to analyze the improvement of 2D dies drafting efficiency through full integration using Siemens NX 7.5. The method used in this research is the fishbone diagram method to identify the root causes of the problems. The research object involved four dies processes, with an initial average drafting time of 36 hours, which was reduced to 16 hours after implementation. The results showed an efficiency improvement of 55.6%, a reduction in the potential for data synchronization errors, and a decrease in additional software usage costs. The implementation of drafting standards, NX templates, work instructions, and internal training became the main factors contributing to the success of this improvement.